Financial Fundamental Analysis Of Vanamei Shrimp Farms With Various Concentrations - Ira Nurdiani; Sriyono Sriyono; Herlinda Maya Kumala Sari (Yayasan Riset dan Pengembangan Intelektual, 2024)
The market needs for vanamei shrimp become less optimal due to constraints on expenditure costs during cultivation, one of which is the minimal cost of buying or renting pond land and the need for vanamei shrimp probiotics. Vanamei shrimp farming business using round ponds is one alternative in cost efficiency. The provision of probiotic composition is expected to be able to provide optimal income for this cultivation business. The purpose of this study was to determine how much influence the provision of probiotic composition calculated into expenditure costs on the income of vanamei shrimp ponds in round ponds. The research method used was quantitative in 10 round ponds of vanamei shrimp farming ponds with 5 different probiotic concentration treatments. The data analysis used was variance analysis, variation coefficient, and 5% LSD test. The results showed, that F Count > F Table 5% or 15.94 > 6.39. This shows that the administration of different probiotics can have a real effect on cultivation income at a significant level of 0.05. Then the value of the variation coefficient is included in the medium category with a value of 14%. In the 5% LSD test, the pool with a mixture of Trichoderma and Nitrosomonas probiotic treatment was the best treatment than the other four treatments by comparing the difference in production costs (variable) used and income obtained.